KONFLIK RUMAH TANGGA DALAM PERSPEKTIF FIKIH MUNAKAHAT - Novi Annisa Nisa (Yayasan Baitul Hikmah al-Zain, 2024)
This study aims to identify the experience of survivors of violence through the phases of the domestic violence cycle and the meaning of life obtained after the experience of violence committed by the husband. The research method used is a qualitative method with a descriptive case study approach. The data collection technique used Liblary Research methods conducted on women survivors of domestic violence. This research focuses on the phases in the cycle of violence as well as the sources, aspects, and factors of meaningfulness of life. The results of this study are that all victims of domestic violence experience all three phases in the cycle of violence. The tension formation phase is characterized by the beginning of conflict triggers such as economic factors, in-law or in-law interference, the emergence of verbal attacks. The acute violence phase is the peak of violence marked by the behavior of damaging goods and committing piresical violence. The honeymoon phase is marked by the husband apologizing to his wife and promising not to repeat his actions again. The meaning of life of the victims was found through creative value, appreciation value. and attitude value. Internal factors such as self-understanding, the ability to change attitudes to be more positive, do purposeful activities, and have a commitment to survive life and achieve their goals. External factors are social support. There are also aspects that become benchmarks in the process of finding the meaning of life of the informants such as kruncing their purpose in life, having life satisfaction, freedom of will, attitude towards death, thoughts about suicide, and feeling worthy of the life they live. Most of the emphasized personal happiness, focus on carrying out their roles and responsibilities as good parents, and appreciation for their children's growth and development. Penelitian ini bertujuan mengidentifikasi pengalaman penyintas kekerasan melalui fase-fase siklus kekerasan dalam rumah tangga dan makna hidup yang diperoleh pasca pengalaman kekerasan yang dilakukan oleh suami. Metode penelitian yang digunakan yaitu metode kualitatif dengan pendekatan studi kasus deskriptif. Teknik pengumpulan data menggunakan metode studi kepustakaan yang dilakukan terhadap perempuan korban penyintas KDRT. Penelitian ini berfokus pada fase-fase dalam siklus kekerasan serta sumber-sumber, aspek, dan faktor kebermaknaan hidup. Hasil dari penelitian ini adalah semua korban KDRT mengalami ketiga fase dalam siklus kekerasan. Fase pembentukan ketegangan ditandai dengan awal mula pemicu terjadinya konflik seperti faktor ekonomi, campur tangan mertua atau ipar, munculnya serangan verbal. Fase kekerasan takut adalah puncak terjadinya kekerasan yang ditandai dengan perilaku merusak barang dan melakukan kekerasan fisik. Fase bulan madu ditandai dengan perilaku meminta maaf dari suami terhadap istri dan berjanji tidak akan mengulangi perbuatannya lagi. Makna hidup para korban ditemukan melalui nilai kreatif, nilai penghayatan, dan nilai sikap. Faktor intemal seperti pemahaman terhadap diri sendiri, kemampuan mengubah sikap menjadi lebih positif, melakukan kegiatan yang terarah, dan memiliki komitmen untuk bertahan menjalani kehidupan dan mencapai tujuannya. Faktor eksternal yaitu adanya dukungan sosial. Terdapat pula aspek aspek yang menjadi tolak ukur dalam proses penemuan makna hidup para narasumber seperti mengetahui tujuan hidupnya, memiliki kepuasan hidup, kebebasan dalam berkehendak, sikap terhadap kematian, pikiran tentang bunuh diri, dan merasa pantas atas hidup yang dijalaninya. Sebagian besar narasumber menekankan pada kebahagiaan pribadi, fokus menjalankan peran dan tanggung jawab sebagai orang tua yang baik, dan penghargaan terhadap pertumbuhan dan perkembangan anak.